Prediction of Minimum Fluidisation Velocity Using a CFD-PBM Coupled Model in an Industrial Gas Phase Polymerisation Reactor - Akbari , Vahid; Hamid, Mohd. Kamaruddin Abd. (Taylor's University, 2014)
The objective of this paper is to develop computational fluid dynamic (CFD)- population balance model (PBM) coupled model to predict a minimum fluidisation velocity in industrial polydisperse gas phase linear low-density polyethylene (LLDPE) polymerisation reactor. The population balance model (PBM) by direct quadrature method of moment (DQMOM) implemented in CFD framework was used to predict the minimum fluidisation velocity. The simulation results were validated by the operational data in terms of bed height and pressure drop. This CFD-PBM coupled model can be extended to investigate the flow field and particle kinetic through the reactor.